Butyric Acid Ameliorates Myocardial Fibrosis by Regulating M1/M2 Polarization of Macrophages and Promoting Recovery of Mitochondrial Function - Li, Xiaogang; Li, Ruixuan; You, Nana; Zhao, Xiexiong; Li, Jiaying; Jiang, Weihong (Frontiers in Nutrition, 2022)
Background: We aimed to investigate the effect and mechanism of butyric acid on rat myocardial fibrosis (MF). Methods: 16S rRNA sequencing was used to analyze the gut microbiota characteristics of the Sham group and MF group. HPLC was applied to measure butyric acid in the feces and serum. In vitro, rat macrophages RMa-bm were stimulated with LPS and IL-4, respectively, and then butyrate was added to study the influences of butyrate on M1/M2 polarization and mitochondrial function of rat macrophages. The rat macrophages and rat myocardial fibroblasts were co-cultured to explore the effect of butyrate on rat myocardial fibroblasts. In addition, MF rats were fed with butyric acid diet. Results: Compared with the Sham group, collagen deposition in the MF group was increased, and fibrosis was serious. The abundance of Desulfovibrionaceae and Helicobacteraceae in the MF group was increased compared with the Sham group. Gut epithelial cells were destroyed in the MF group compared with the Sham group. Compared with the Sham group, LPS content in the MF group was increased and butyric acid was decreased. Butyrate inhibited M1 and promoted M2. Furthermore, butyrate may promote mitochondrial function recovery by regulating M1/M2 polarization of macrophages. After adding butyrate, cell proliferation ability was decreased, and aging and apoptosis were increased, which indicated that butyrate inhibited rat myocardial fibroblasts activity. Moreover, butyric acid could protect mitochondria and improve the symptoms of rats with MF. Conclusions: Butyric acid ameliorated MF by regulating M1/M2 polarization of macrophages and promoting recovery of mitochondrial function.